KONSELING INDIVIDU MELALUI PENDEKATAN CLIENT CENTERED THERAPY DALAM MENGATASI INDISIPLINER SISWA - Yuli Nugrahanti, Ardita; Sukoco, Dewin; Silahudin, rizky (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
Disobedient or disciplinary behavior is an action carried out by an individual or society that violates norms, rules or laws. We also often encounter behavior like this at school. In almost every school there are students who break school rules even though there are clear rules and receive punishment, but they still break them. One of the violations is skipping school, there are students who deliberately leave school or skip school just to play outside or not come in without clear explanation. In providing treatment for this problem, there is an individual counseling service which provides treatment to student for violations committed in the hope of making students comply with existing rules again. By using a client centered therapy approach, a guidance and counseling teacher only directs or becomes a facilitator so that students can solve their own problems. In this research, we used this method to deal with students who skipped school at SMA Negeri 1 Kedunggalar with clients from class XII.